Cover Image, Volume 77, Issue 3‐4. Issue 3 (7th April 2020) - Aiken, Jayne; Buscaglia, Georgia; Aiken, A. Sophie; Moore, Jeffrey K.; Bates, Emily A.
Abstract : ON THE COVER : The front cover image is based on the Commentary Article Tubulin mutations in brain development disorders: Why haploinsufficiency does not explain TUBA1A tubulinopathies by Emily Bates et al., https://doi.org/10.1002/cm.21567 .